Beyond Scandal and Shame? Ecclesiology and the Longing for a Transformed Church. (September 2019) - Lennan, Richard
The need for reform of the Catholic Church's structures features prominently in discussion of the clerical sexual abuse scandal. Less common has been reflection on the challenge that the crisis presents to ecclesiology, to considering the church theologically. This article addresses that challenge. It engages three tasks—facing the church's brokenness; understanding the church in terms of grace and human freedom; and facilitating the participation of all the church's members—that are necessary for an ecclesiology able to be both realistic and hopeful in the current circumstances.